The Extent of Arbitration's Preference and Independence over the Judicial System in Disputes Resolution Selection: A Re-Evaluation for Developing Judiciary and Arbitration Systems - Ahmed, Ahmed Salem (IAIN Samarinda, 2019)
The arbitration system is considered to be the most effective and efficient way of dispute resolution than the judicial litigation system. This opinion is based on several reasons such as time speed, confidentiality, flexibility, and so forth. Therefore, arbitration is considered to be able to present preference and independence in dispute resolution. However, this assumption needs to be assessed scientifically in accordance with existing realities. Hence, this article is to compare between the arbitration and other litigation systems in terms of their advantages and disadvantages. It found that arbitration was present in response to the weaknesses of the rigid justice system and its lack of creativity in creating mechanisms for disputes between disputing parties. Despite the fact, the arbitration system, in some cases, does not have independence precisely because of its flexibility, confidentiality and lack of supervision. Thus this article confirms that the actual arbitration system does not have preferences and independence that far exceeds the general litigation justice system. In other words, the advantages of the arbitration system do not exceed that of the general justice system except for its flexibility in handling unique disputes.Keywords: Arbitration system – Judicial system – needs of developing for resolving the disputes.